Etiology of Students Fail to Complete Doctorate Degree within Stipulated Time - Muhammad Irshad, (PJE, 2023)
In the face of contemporary world requirements, the demand for a research degree is highly aggravated. In order to fulfill the growing demand academia enrolled candidates with such distinctive characteristics like self-motivated, long studying/working stamina coupled with strong family support. The failures of such distinguish characteristics students postulate long-lasting effect on society in general and academia in particular.